RANCANG BANGUN SISTEM PENGEREMAN REM TROMOL PADA SEPEDA LISTRIK BERBASIS ARDUINO UNO R3 - Slamet Riyadi; Leo Anggar Prasetyo; Novita Wulandari (Bajang Institute, 2025)
Braking failure due to overheating is more common in electric bicycles used for long distance travel or in hilly areas. This study prompted manufacturers to develop more effective cooling systems for brakes. (Study from the European Transport Safety Council (ETSC)), the objectives of this research are as follows: To find out how to make a drum brake braking system on an electric bicycle using Arduiono Uno R3 as a teaching tool to understand the function and workings of the system, To detect braking temperature and provide a warning system. This research is generally research that aims to develop a media. The appropriate research method for this research is the Research and Development Method or also known as Research and Development (R&D)